Association between atherogenic index of plasma and new onset of type 2 diabetes among elderly in China: a longitudinal study - He, Xiang-yang; Lu, Zhi-wei; Guo, Yan-Fang; Zhao, Ren-cheng; Liu, Zheng (Frontiers in Endocrinology, 2025)
BackgroundPrevious studies have reported an association between the atherogenic index of plasma AIP and CVD incidence. However, few studies have investigated its longitudinal predictive effect on T2D among elderly individuals.MethodsData from the BaHLS of the Community-Based Elderly Population in Shenzhen, China, were utilized. AIP was calculated as log10 ^[TG/HDL-C]. The subjects were divided into four groups on the basis of the quartiles of AIP values at baseline. A multivariable Cox proportional hazards model and a GAM were employed to assess the longitudinal predictive effect of the AIP on the risk of new-onset T2D. The predictive efficacy of the AIP, TG, and HDL-C for new-onset T2D was analyzed and compared via receiver operating characteristic (ROC) curve analysis.ResultsA total of 18,295 subjects were selected, of whom 1,300 developed T2D by 2022. After adjusting for confounding factors, we found that the AIP was positively associated with the incidence of T2D. When AIP was categorized into four groups based on quartiles, the risk of new-onset T2D in the 2nd to 4th groups increased by 26% (95% CI: 4%, 52%), 40% (95% CI: 17%, 68%), and 57% (95% CI: 31%, 87%) compared with that in the 1st group, respectively. The AUCs for AIP, TG, and HDL-C were 0.601 (95% CI: 0.586 - 0.617; p < 0.001), 0.589 (95% CI: 0.573 - 0.605; p < 0.001), and 0.567 (95% CI: 0.551 - 0.584, p < 0.001), respectively. A nonlinear association was observed between the AIP score and the risk of new-onset T2D. In patients with an AIP ≤ 0, an increase in the AIP was significantly associated with an increased risk of T2D. The relationship between the AIP score and the risk of new-onset T2D persisted across most subgroups.ConclusionThe study demonstrated that the AIP was positively associated with an increased incidence of T2D, suggesting that the AIP should serve as a valuable indicator for monitoring and preventing new-onset T2D.